2020
DOI: 10.1021/acsaelm.0c00109
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Electromagnetic Shielding Properties of Lightweight and Porous Multifunctional Layers

Abstract: The preparation of functional fabrics with enhanced electrical properties requires suitable selection of surface modification and particulate systems as fillers. The best choice would be to use materials with low fiber diameters, good shape stability, and comfort-related properties. In this study, a composite nonwoven fabric "Milife" with surface covering by a particulate-based copper layer was investigated. Electromagnetic, electrical, and transport characteristics of the prepared materials were evaluated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In addition to Cu, oxygen (O), carbon (C), calcium (Ca), and titanium (Ti) are visible, and their concentration is presented in Figure 5 . The presence of titanium is due to the matting of polyester by TiO 2 before creating a MILIFE structure [ 22 ]. It is observed that the copper coating is not continuous, but distances between coated parts are over the percolation threshold.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Cu, oxygen (O), carbon (C), calcium (Ca), and titanium (Ti) are visible, and their concentration is presented in Figure 5 . The presence of titanium is due to the matting of polyester by TiO 2 before creating a MILIFE structure [ 22 ]. It is observed that the copper coating is not continuous, but distances between coated parts are over the percolation threshold.…”
Section: Resultsmentioning
confidence: 99%
“…The copper deposit was about 3 g·m −2 , dependent on the planar weight of Milife. Copper-coated Milife has enhanced reflectance in the FIR region, and untreated Milife is sufficiently transparent for the NIR range (sun radiation) [ 26 ]. The structure of copper-coated Milife is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Both layers are thermally bonded together (see Figure 6 a). MILIFE is a promising material for surface metals deposition because it is composed of a dense network of monofilaments connected by fixed points [ 22 , 23 ]. Plasma pretreatment with autocatalytic activation can be used for copper deposition (see Figure 6 b) from a strong alkaline bath containing copper salts and a reduction agent (borohydride).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Plasma pretreatment with autocatalytic activation can be used for copper deposition (see Figure 6 b) from a strong alkaline bath containing copper salts and a reduction agent (borohydride). The copper surface concentration is about 3 g m −2 [ 23 ].…”
Section: Literature Reviewmentioning
confidence: 99%